MENELISIK MAKNA SYAJARAH DALAM AL-QUR’AN: (Analisis Semantik Toshihiko Izutsu) - Sihombing, Muhammad Ebin Rajab (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2023)
The ongoing discourse regarding the interpretation of "syajarah" in the Qur'an lacks a consensus. This is evident in the diverse array of perspectives and explanations surrounding its meaning. Consequently, the author delves deeper into an examination of the semantic analysis of "syajarah" using Toshihiko Izutsu's approach. The selection of this methodology is rooted in Izutsu's semantic framework, which provides a platform for exploring the nuanced meanings of a word. A pivotal aspect of this investigation is to scrutinize the semantic dimensions of "syajarah." The author employs a qualitative methodology, specifically a literature study, to navigate this exploration. The data utilized encompasses information gleaned from various sources, including books, journal articles, and electronic documents, bolstering the research process. This inquiry reveals that the fundamental meaning of "syajarah" is 'tree.' The syntagmatic relational meanings include associations with Allah, Naha, Syaitan, Zalim, and Masalan. In terms of paradigmatic meaning, the words Nabat and Zuru' come into play. While the synchronic and diachronic meanings of "syajarah" have experienced temporal shifts, the core meaning has remained relatively stable. Furthermore, diverse interpretations generally align with the basic meaning of "syajarah," with the exception of Quraish Shihab, who suggests a figurative understanding in the context of the Prophet Adam's story. Notably, when coupled with the word "taqrabu," the figurative interpretation of "syajarah" emerges, implying actions that may lead to social harm.